"Together we can make it better": Collective action and governance in a girls' ice hockey association. (December 2013) - Stevens, Julie; Adams, Carly
This paper, drawing on collective action literature and situated within the women's sport movement, offers a case study of a separate girls' minor hockey association that formed in Ontario in the mid-1990s. The analysis explores the process of establishing a girls' hockey association that is separate from the boys' minor hockey umbrella. Two fundamental collective action themes emerged from the data. First, the data revealed the founders of the separate association acted according to both affective and rational motives. Second, the founders utilized different strategies, namely advocacy and social action, to form the association. These findings support an integrated perspective towards community change as it pertains to female hockey governance, and introduces a novel stream of inquiry into this area of female sport – one that connects collective action, governance, and organizational dynamics.